The Influence of Store Atmosphere and Sales Promotion on Impulse Buying at Lima Rasa Café During the Covid-19 Pandemic - Gradiyanto, Adrian; Pangestu, Arini Dewi; Putri, Isabella Monica; Nurbasari, Anny (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
This study aims to test and analyze the effect of store atmosphere and sales promotions on the impulse buying of five flavors café during the Covid-19 pandemic. Data collection in this study used a survey method with an air questionnaire built using a Likert scale. The sample of this research was 300 respondents who were selected using purposive sampling with the criteria of respondents being consumers of Café Lima Rasa in Bandung City. The research model was built and analyzed using the Structural Equation Modeling (SEM) analysis method. The research data were analyzed using Smart PLS software. Based on the hypothesis testing, it was found that store atmosphere and sales promotion did not have a positive effect on impulse buying, and sales promotion had a positive effect on impulse buying. For this reason, the researcher suggests that Cafe Lima Rasa's management increase sales promotions to increase impulse buying, especially using social media, considering that based on the results of descriptive statistics, Café Lima Rasa's consumers are mostly young people. The management of Café Lima Rasa should also design a better store atmosphere so that the cafe's appearance becomes more Instagram-able and can support sales promotions.